Literatur Review : Strategi Coping yang digunakan oleh Korban Bencana Alam Gempa Bumi yang Mengalami PTSD - Mutiara Rahma Eldita; Kartika Aulia Rahmi; Faisal Kurnia; Zahwa Saviola Ramadhini; Lidya Yuliani (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
The frequent earthquakes in Indonesia have had complex impacts, not only on physical damage and material losses, but also on the psychological aspects of survivors. One psychological problem that often arises is Post-Traumatic Stress Disorder (PTSD), which can disrupt mental health, quality of life, and an individual's ability to return to normal activities. This condition requires appropriate treatment, one of which is through providing effective coping strategies for survivors. The purpose of this study is to collect and review knowledge related to coping strategies used by earthquake disaster victims who experience PTSD. This study uses a literature review approach by exploring various relevant scientific sources that are in line with the topic. The analysis process was carried out using the content analysis method, namely an in-depth discussion of the data with reference to the stress coping theory proposed by Lazarus and Folkman. The results of the study indicate that each region, both in Indonesia and in various countries, has a different approach to coping strategies to overcome PTSD in earthquake victims. These differences are influenced by culture, social values, community support, and available resources. In general, the identified coping strategies fall into two main categories: problem-focused coping (active coping), which focuses on solving problems, and emotion-focused coping (passive coping), which focuses on managing emotions resulting from trauma. These findings confirm that a combination of these two strategies, tailored to individual characteristics and cultural context, can be an effective approach to the psychological recovery of earthquake survivors.